Training modification decision-making and the role of athlete monitoring in elite endurance sports coaching: An instrumental case study of a world-class cycling coach and a world-class development rowing coach - Timmerman, W. P.; Stanley, M.; Raynor, A.; Lawler, N.; Abbiss, C. (Journal of Science and Cycling, 2025)
The purpose of this study is to improve the understanding of the training modifications made by elite endurance coaches and explore the role athlete monitoring has in this process. Using Stake`s (1995, 2003) case study methodology, an instrumental case study design was employed to allow naturalistic generalisations to be drawn when exploring endurance sports coaching and athlete monitoring at the elite level. The study followed a world-class cycling coach and a world-class development rowing coach for six months, and data collection included four semi-structured interviews, eleven retrospective verbal reports through stimulated recall, and eight field observations of training sessions. A qualitative analysis consisting of categorical aggregation and direct interpretation generated three themes regarding coaches` athlete monitoring and training modifications: 1) Gathering and balancing information for continuous situational assessment and training modification triggers; 2) The only constant in coaching is change: Anticipating modifications and being ready for the unexpected; 3) Empowering athlete autonomy of training modification decision-making within coach boundaries. The findings indicated that minor to moderate training modifications were predominantly reactive to subjective athlete feedback and disruptive events, while major training modifications were predominantly in response to crisis events. Quantitative monitoring data alone rarely dictated a training modification unless there were concerns about the athlete`s honesty, however, quantitative information led to gathering additional qualitative information through intensified coach-athlete communication and coach observation of the athlete. The findings also highlighted that athlete monitoring had a central role in modifying training, yet non-athlete monitoring information such as weather, logistics, and organisational decisions was frequently the decisive information. Further, coaches demonstrated adaptability to changing circumstances through anticipatory conditional decision-making. This was done by establishing multiple decision paths in advance and, depending on the athlete monitoring outcome, selecting the most appropriate course of action. Additionally, the coaches empowered their athletes and gave them the autonomy to make minor to moderate training modifications within the coach`s boundaries. Lastly, the cross-case differences reflected sport-specific and organisational factors in training modifications and showed a higher injury incidence of the under-23 rowers compared to the professional cyclists, which may be related to the experience of the athletes.